Assessment of Hepatitis E virus transmission risks: a comprehensive review of cases among blood transfusion recipients and blood donors - Sangthang Singson; Shamee Shastry; N. Sudheesh; Kiran Chawla; Mridula Madiyal; Dhivya Kandasamy; Chiranjay Mukhopadhyay (Infection Ecology & Epidemiology, 2024)
Background Hepatitis E Virus is a major cause of acute and fulminant hepatitis, particularly in developing countries. While the virus is commonly spread through the fecal-oral route, numerous cases of transfusion transmitted Hepatitis E Virus (TT-HEV) have been reported, raising concerns about its transmission via blood transfusions, especially in industrialized countries. The high prevalence of antibodies and viremia among asymptomatic blood donors further heightens the risk of transfusion-related transmission. However, there is still debate about the best strategy to minimize TT-HEV.Objective The review was conducted to Summarize the literature on TT-HEV infection cases and the prevalence of HEV among blood donors.Methods The databases PubMed, Scopus, Web of Science, Embase, and CINAHL were searched for relevant studies from 2000 to 2022.Serological and molecular screening data of HEV in blood donors were used to gather prevalence and incidence rates.TT-HEV cases were reviewed by examining evidence of HEV infection before and after transfusion.Results A total of 121 manuscripts reports the prevalence and incidence of HEV among blood donors and cases of TT-HEV. Twenty-six articles reported confirmed cases of TT-HEV and 101 articles reported on HEV prevalence or incidence among blood donors.Conclusion TT-HEV transmission through blood products is a real concern, especially for immunocompromised patients.The risk and severity of infection could vary between immunocompetent and immunosuppressed patients.To increase transfusion safety, the evaluation recommends HEV screening protocols, especially in endemic region.